Transfer to community and prison mental health care from Ireland’s main remand prison over three years: 2015-2017 - Walsh, Jamie; Smith, Damian; Byrne, Fintan; Hickey, Philip; Taylor, Enda; Caddow, Martin; Reynolds, Orla; O’Neill, Conor (Frontiers in Psychiatry, 2024)
Background The post-release period is associated with an increased risk of morbidity and mortality. Previous studies have identified deficits in pre-release planning for mentally ill people in prison, particularly in remand settings. Objectives We aimed to determine the proportion of mentally ill people in Ireland’s main remand prison who were referred for mental health follow up in community and prison settings, who achieved face to face contact with the receiving service. Method This retrospective observational cohort study was based in Ireland’s main male remand prison, Cloverhill. Participants included all those individuals on the caseload of the prison inreach mental health team who were referred for mental health follow up in community and prison settings at the time of discharge, prison transfer or release from custody over a three-year period, 2015 - 2017. Successful transfer of care (TOC) was defined as face-to-face contact with the receiving service, confirmed by written correspondence or by follow up telephone call. Clinical, demographic and offence related variables were recorded for all participants. Results There were 911 discharges from the prison inreach mental health team within the three-year study period. Of these, 121 were admitted to hospital, 166 were transferred to other prison inreach mental health services and 237 were discharged to community based mental health follow up in psychiatric outpatient or primary care settings. One third (304/911) had an ICD-10 diagnosis of schizophreniform or bipolar disorder (F20–31) and 37.5% (161/911) were homeless. Over 90% (152/166) of those referred to mental health teams in other prisons achieved successful TOC, with a median of six days to first face-to face assessment. Overall, 59% (140/237) of those referred to community psychiatric outpatient or primary care services achieved TOC following referral on release from custody, with a median of nine days from release to assessment. Clinical and demographic variables did not differ between those achieving and not achieving successful TOC, other than having had input from the PICLS Housing Support Service. Conclusion Successful transfer of care can be achieved in remand settings using a systematic approach with an emphasis on early and sustained interagency liaison and clear mapping of patient pathways. For incarcerated individuals experiencing homelessness and mental health disorders, provision of a housing support service was associated with increased likelihood of successful transfer of care to community mental health supports.